Gate-bias and temperature dependence of charge transport in dinaphtho[2, 3-b:2′, 3′-d]thiophene thin-film transistors with MoO3/Au electrodes. (20th February 2018) - Shaari, Safizan; Naka, Shigeki; Okada, Hiroyuki
Abstract: We investigated the gate-bias and temperature dependence of the voltage–current ( V – I ) characteristics of dinaphtho[2, 3- b :2′, 3′- d ]thiophene with MoO3 /Au electrodes. The insertion of the MoO3 layer significantly improved the device performance. The temperature dependent V – I characteristics were evaluated and could be well fitted by the Schottky thermionic emission model with barrier height under forward- and reverse-biased regimes in the ranges of 33–57 and 49–73 meV, respectively. However, at a gate voltage of 0 V, at which a small activation energy was obtained, we needed to consider another conduction mechanism at the grain boundary. From the obtained results, we concluded that two possible conduction mechanisms governed the charge injection at the metal electrode–organic semiconductor interface: the Schottky thermionic emission model and the conduction model in the organic thin-film layer and grain boundary.